How we learn learning and non-learning in school and beyond - Illeris, Knud (London Routledge, 2007)
Deals with the fundamental issues of the processes of learning, critically assessing different types of learning and obstacles to learning. This book provides a comprehensive introduction to both traditional learning theory and the international research into learning processes.
The basis of the understanding of learning -- The processes and dimensions of learning -- Different types of learning -- The content dimension of learning -- The incentive dimension of learning -- The interaction dimensions of learning -- Learning as whole -- Barriers to learning -- Learning, dispositions and preconditions -- Learning and life course -- Learning in different learning spaces -- Learning, education and society.
Keywords: Learning, Psychology of; Cognitive learning; Social learning